Analisis Vo2Max Tim Sepak Bola Persebaya Putri Pada Kegagalan Piala Pertiwi 2021 - Fara Nindiya Wardani; Heri Wahyudi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the Vo2Max condition of Persebaya Putri football players at the 2021 Pertiwi Cup, which from the results of this analysis can be used as a reference for performance during the match. This is also based on the results of the 2021 Pertiwi Cup where Persebaya Putri failed and did not qualify in the grub phase, and in every match they always conceded in the second half and were able to play stably in the first 45 minutes. This study uses a quantitative descriptive method. To analyze the data using the Statistical Program for Social Science or called SPSS. It will be carried out by the Persebaya Putri team in 2022 at the Ngelom Sepanjang Sidoarjo Rusunawa Field, with a population of 29 players. With a sample of 20 athletes from the age range of 17 years and over. From the results of the analysis, as many as 8 players fall into the less category, 8 players fall into the medium category and 4 players fall into the good category. From this study, the average Vo2Max of Persebaya Putri players was 30 and there were 10 players who had Vo2Max below the team's average. This is a factor that hinders the players from continuing to play stablyx until the end of the match, so that it can trigger the failure of the Persebaya Putri team in the 2021 Pertiwi Cup.